Travel app shopping on smartphones: understanding the success factors influencing in-app travel purchase intentions - Lim, Xin Jean; Cheah, Jun Hwa; Morrison, Alastair M.; Ng, Siew Imm; Wang, Siqi (Emerald Group Publishing, 2022)
With the diffusion of innovation theory (DOI) and theory of planned behaviour (TPB) as the guiding theoretical perspectives, this research aims to identify the factors motivating user attitudes and in-app purchase intentions (IAPIs). The moderating impact of user inertia towards TPB constructs was also explored. A total of 500 responses were received via an online survey fielded from July to October 2021. The data were then analysed using partial least square structural equation modeling (PLS-SEM). The results indicated that attitudes towards travel app shopping were predominantly determined by perceived relative advantages, compatibility and complexity. Findings also suggested that IAPIs are positively influenced by attitudes, communicability and perceived behavioural control and are moderated by user inertia. A holistic framework integrating theoretical foundations from two disciplines (information systems and psychology) was designed to explain factors motivating user intentions to purchase travel products and services from apps. This research found a missing link in previous studies by showing the indirect role of attitudes that bridges the DOI and TPB and the importance of inertia as a key boundary condition.